Data from: Odour cues influence predation risk at artificial bat roosts in urban bushland - Threlfall, Caragh; Law, Bradley; Banks, Peter B.; Banks, P. B.; Threlfall, C. (2013)
Odours that accumulate from roosting can attract predators and increase predation risk. Consequently, selection should favour strategies that allow prey to evade detection by predators, including changing roosts. Insectivorous bats that roost in tree hollows regularly switch roosts and roost in different sized groups: strategies that would alter the accumulation of roost odours and are hypothesized to reduce predation risk. We experimentally manipulated the amount and refresh rate of roosting odour cues at 90 artificial bat roosts in Sydney, Australia, to test the hypothesis that odours increase predator visitation. Predators visited roosts with bat faeces significantly more often than untreated control roosts. Roosts with small amounts of faeces mimicking sites used by solitary bats had the greatest rate of visitation. This suggests that bats roosting alone, rather than in groups, have a greater likelihood of disturbance or predation. Roost switching likely decreases the predictability of finding occupied roosts, however we show that all roosts (those currently or recently occupied) were visited by predators, suggesting generalist urban predators readily investigate potential roosts. This is the first demonstration that bat odours are attractive to predators that use olfactory cues, showing that bats are at risk of predation in visually cryptic roosts. CThrelfall_DATA_Nest_Predation_2010Raw data collected in the field from a nest predation experiment. The metadata tab describes more detail about when and how the data was collected.